The Significance and Motif of Lombok Weaving : A Comparative Analysis of Tradisional and Automated Machine Techniques as a Culture Diversity Learning - Elnawati Elnawati; deviana mayasari; zedi muttaqin (Sosial Budaya, 2024)
Handwoven fabrics, commonly known as "kain tenun," have been an enduring part of the cultural heritage of the Sasak community, passed down through generations and frequently utilized in various traditional and religious ceremonies. Cultural tourism has played a pivotal role in inspiring the younger generation to delve into the tradition of weaving due to their increasing interest in the popular trend of cultural tourism. This research aims to explore and compare the meanings of traditional Lombok weaving motifs with the outcomes of automated machine production as part of cultural diversity education in the textile context. A qualitative method is employed, utilizing the Informant Technique determined through purposive sampling to obtain in-depth perceptions of the cultural values inherent in traditional Lombok weaving and machine-produced textiles. Research instruments include observation sheets and interview guidelines. Data are analyzed using the Miles and Hubberman method to compare and present the meanings of traditional Lombok weaving motifs with machine-produced outcomes. The research findings reveal that traditional Lombok weaving motifs hold strong cultural, historical, and symbolic values for the local community. Pringgasela village exhibits a diverse array of motifs, with Sri Menanti, Sundawa, Pucuk Rebong, Ragi Bayanan, and Pancor Boros emerging as motifs most sought after by tourists and serving as distinctive features of Pringgasela. The positioning of motifs or symbols in weaving acts as a symbolic intermediary between human thought and the surrounding reality. These motifs can be utilized as educational tools to shape the profile of Pancasila students, aligning with the philosophical meanings inherent in each weave. For instance, the Pucuk Rebong motif embodies characteristics of faith and piety towards the Almighty, while Sri Menanti signifies creativity, Ragi Bayanan represents independence, and motifs such as Sundawa represent a blend, reflecting global diversity. This insight can be considered a national perspective or a new realm of knowledge for external communities.